Altered pain modulation in patients with persistent postendodontic pain. Issue 10 (October 2015) - Nasri-Heir, Cibele; Khan, Junad; Benoliel, Rafael; Feng, Changyong; Yarnitsky, David; Kuo, Fengshen; Hirschberg, Craig; Hartwell, Gary; Huang, Ching-Yu; Heir, Gary; Korczeniewska, Olga; Diehl, Scott R.; et al.
Abstract : Abstract: Persistent pain may follow nerve injuries associated with invasive therapeutic interventions. About 3% to 7% of the patients remain with chronic pain after endodontic treatment, and these are described as suffering from painful posttraumatic trigeminal neuropathy (PTTN). Unfortunately, we are unable to identify which patients undergoing such procedures are at increased risk of developing PTTN. Recent findings suggest that impaired endogenous analgesia may be associated with the development of postsurgical chronic pain. We hypothesized that patients with PTTN display pronociceptive pain modulation, in line with other chronic pain disorders. Dynamic (conditioned pain modulation, temporal summation) and static (response to mechanical and cold stimulation) psychophysical tests were performed intraorally and in the forearm of 27 patients with PTTN and 27 sex- and age-matched controls. The dynamic sensory testing demonstrated less efficient conditioned pain modulation, suggesting reduced function of the inhibitory endogenous pain-modulatory system, in patients with PTTN, mainly in those suffering from the condition for more than a year. The static sensory testing of patients with PTTN demonstrated forearm hyperalgesia to mechanical stimulation mainly in patients suffering from the condition for less than a year and prolonged painful sensation after intraoral cold stimulus mainly in patients suffering from the condition for more than a year. These findings suggest that PTTN is associated more with the inhibitory rather than the facilitatory arm of pain modulation and that the central nervous system has a role in PTTN pathophysiology, possibly in a time-dependent fashion. Abstract : Patients suffering from persistent pain after endodontic treatment have less efficient pain modulation system compared with healthy controls.